EMBRYO SAC DEVELOPMENT 1 affects seed setting rate in rice by controlling embryo sac development. Issue 2 (5th March 2021) - Wang, Tiankang; Li, Yixing; Song, Shufeng; Qiu, Mudan; Zhang, Licheng; Li, Chengxia; Dong, Hao; Li, Lei; Wang, Jianlong; Li, Li
Abstract: Seed setting rate is one of the critical factors that determine rice yield. Grain formation is a complex biological process, whose molecular mechanism is yet to be improved. Here we investigated the function of an OVATE family protein, Embryo Sac Development 1 (ESD1), in the regulation of seed setting rate in rice ( Oryza sativa ) by examining its loss-of-function mutants generated via clustered regularly interspaced short palindromic repeats (CRISPR)/CRISPR-associated9 (Cas9) technology. ESD1 was predominantly expressed at Stage 6 of panicle development, especially in the ovules. esd1 mutants displayed reduced seed setting rates with normal stamen development and pollen tube growth but abnormal pistil group. Investigation of embryo sacs revealed that during the mitosis of functional megaspores, some egg cells degraded during differentiation in esd1 mutants, thereby hindering subsequent fertilization process and reducing seed setting rate. In addition, the transcriptional level of O. sativa anaphase-promoting complex 6, a reported embryo sac developing gene, was significantly reduced in esd1 mutants. These results support that ESD1 is an important modulator of ESD and seed setting rate in rice. Together, this finding demonstrates that ESD1 positively regulates the seed setting rate by controlling ESD in rice and has implications for the improvement of rice yield. Abstract : EMBRYO SAC DEVELOPMENT 1 regulates the seed setting rate by controlling embryo sac development in rice and has implications for the improvement of rice yield.